From the ‘Jumpers in Maine’ to the ‘Boy from Paris’: the life of Georges Gilles de la Tourette and the first description of tic disease - Damjanović, Radomir; Jovanović, Nikola; Aleksić , Dejan; Stamenović, Jelena (Vojnosanitetski pregled, 2026)
In 1885, French neuropsychiatrist Dr. Georges Gilles de la Tourette was the first to describe a disease of tics. His success was not unexpected, as he was a student of the renowned neurologist Dr. Jean-Martin Charcot. Georges Gilles de la Tourette was born on October 30, 1857, in Saint-Gervais-les-Trois-Clochers, France, as the eldest of four children. Immediately after graduating in 1881, he went to Paris for further training. His special interests included hysteria, psychotherapy, and hypnotism. By revising an article titled “Experiments with the ‘Jumpers of Maine’ ”, he concluded that a somewhat similar disorder exists in different cultures across the world. He soon described additional signs of the syndrome, including inarticulate sounds, echolalia, and coprolalia, and accentuated the hereditary nature of the disease. Insightful and dedicated yet short-tempered and arrogant, Georges Gilles de la Tourette was an inspiring physician and teacher. He left behind a significant legacy in the study of involuntary movements, particularly through his description of the syndrome that would come to be known as Tourette syndrome. This description of the syndrome is just a portion of his contributions to neurology and psychiatry. His work, often met with both admiration and criticism, reflects the complexities of his personality and the challenges he faced in his professional life.
Keywords: dyskinesias; history of medicine; history, 19th century; tourette syndrome.